Assessing the Environmental Benefits of Urban Transport Integration: A Comprehensive Review - Aris Krisdiyanto (Science and Applied Journal (SIAP), 2024)
Urban transportation integration plays an important role in influencing greenhouse gas (GHG) emissions in developing and developed cities. This systematic literature review analyzes the impact of urban transport integration on GHG emissions by comparing the two types of cities. Through literature searches and analysis, the characteristics of developing and developed cities, the challenges of implementing urban transport integration, as well as solutions that can be implemented to overcome these challenges have been identified. The results show that urban transport integration has significant potential in reducing GHG emissions, especially through the promotion of sustainable transport and compact urban planning. The implications of this research highlight the importance of policies that support public transportation and sustainable infrastructure development to reduce GHG emissions and encourage environmentally friendly urban development.